Nilai Pendidikan Tuturan Ritual Ka Nggua pada Masyarakat Paumere Desa Kerirea Kecamatan Nangapanda Kabupaten Ende - Rikardus Pande; Simon Sabon Ola; Agustinus Semiun (Journal on Education, 2023)
This study raises the educational value of the utterances of the Ka Nggua ritual carried out in the life of the Paumere people. This study aims to describe the educational value of the Ka Nggua ritual utterances carried out in the life of the Paumere people which are beneficial for the education of values, character and for the preservation of culture for the local community. The results of this study explain that the educational values contained in the ritual utterances of Ka Nggua, namely (1) the value of religious education as the main value in the life of the Pau mere people, (2) the value of moral education which teaches honesty, sincerity and openness, (3) ethical values teach self-awareness, sensitivity, adaptability, responsibility (4) cultural values that teach respect, inherit and preserve cultural customs, and (5) social education values that teach the nobility of cooperation, mutual cooperation, mutual assistance, mutual respect, cooperation, maintaining unity and brotherhood.